Peptide-Major Histocompatibility Complex Dimensions Control Proximal Kinase-Phosphatase Balance during T Cell Activation - Choudhuri, Kaushik (American Society for Biochemistry and Molecular Biology, 2009)
T cell antigen recognition requires binding of the T cell receptor (TCR) to a complex between peptide antigen and major histocompatibility complex molecules (pMHC), and this recognition occurs at the interface between the T cell and the antigen-presenting cell. The TCR and pMHC molecules are small compared with other abundant cell surface molecules, and it has been suggested that small size is functionally important. We show here that elongation of both mouse and human MHC class I molecules abrogates T cell antigen recognition as measured by cytokine production and target cell killing. This elongation disrupted tyrosine phosphorylation and Zap70 recruitment at the contact region without affecting TCR or coreceptor binding. Contact areas with elongated forms of pMHC showed an increase in intermembrane distance and less efficient segregation of CD3 from the large tyrosine phosphatase CD45. These findings demonstrate that T cell antigen recognition is strongly dependent on pMHC size and are consistent with models of TCR triggering requiring segregation or mechanical pulling of the TCR.